Physical and thermal processing of Waste Printed Circuit Boards aiming for the recovery of gold and copper - Joana Dias (2018)
The recovery of electronic waste to obtain secondary raw materials is a subject of high relevance in the context of circular economy. Accordingly, the present work relies on the evaluation of mining separation/concentration techniques (comminution, size screening, magnetic separation and gravity concentration) alone as well as combined with thermal pre-treatment to recover gold and copper from Waste Printed Circuit Boards. For that purpose, Waste Printed Circuit Boards were subjected to physical processing (comminution, size screening in 6 classes from < 0.425 mm to > 6.70 mm, magnetic separation and gravity concentration) alone and combined with thermal treatment (200-500 degrees C), aiming the recovery of gold and copper. Mixed motherboards and graphic cards (Lot 1 and 3) and highly rich components (connectors separated from memory cards, Lot 2) were analyzed. Gold and copper concentrations were determined before and after treatment. Before treatment, concentrations from 0.01 to 0.6 % wt. and from 9 to 20 % wt. were found for gold and copper respectively. The highest concentrations were observed in the size fractions between 0.425 and 1.70 mm. The highest copper concentration was around 35 % wt. (class 0.425-0.85 mm) and when analyzing memory card connectors alone, gold concentrations reached almost 2% in the same class, reflecting the interest of separating such components. The physical treatment alone was more effective for Lot 1/3, compared to Lot 2, allowing recoveries of 67 % wt. and 87 % wt. for gold and copper respectively, mostly due to differences in particles size and shape. The thermal treatment showed unperceptive influence on gold concentration but significant effect for copper concentration, mostly attributed to the size of the copper particles. Concentrations increased in a factor of around 10 when the thermal treatment was performed at 300 degrees C for the larger particles (1.70-6.70 mm); the best results were obtained at 400 degrees C for the other sizes, when the highest rate of thermal decomposition of the material occurred.